Preservation of intangible and tangible cultural heritage using digital technology - Lanto Ningrayati Amali; Muhammad Rifai Katili; Wandi Ismail (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
There is presently a shortage of preservation of intangible cultural heritage and places for distributing tangible cultural heritage artifacts, regardless of their high value and usability for a nation. Despite efforts to protect cultural heritage, such as mapping and designing information systems to ensure the authenticity of information circulating in the community about intangible traditions and tangible sites obtained from different sources, many historical information places have been converted into new beliefs and buildings. Therefore, this research aims to provide information to promote public awareness about the distribution of tangible sites and intangible information about cultural heritage. A system development method with a prototype model comprising the stages of design and evaluation, system coding, and program testing, alongside system evaluation and usage, was employed. Subsequently, the results showed that the mapping information system increases the effectiveness and efficiency of delivering intangible and tangible cultural heritage information to the public and tourists.